Interaction of ischaemic postconditioning and thrombectomy in patients with ST-elevation myocardial infarction. Issue 1 (17th July 2019) - Nepper-Christensen, Lars; Høfsten, Dan Eik; Helqvist, Steffen; Lassen, Jens Flensted; Tilsted, Hans-Henrik; Holmvang, Lene; Pedersen, Frants; Joshi, Francis; Sørensen, Rikke; Bang, Lia; Bøtker, Hans Erik; Terkelsen, Christian Juhl; et al.
Abstract : Objective: The Third Danish Study of Optimal Acute Treatment of Patients with ST-segment Elevation Myocardial Infarction – Ischaemic Postconditioning (DANAMI-3-iPOST) did not show improved clinical outcome in patients with ST-segment elevation myocardial infarction (STEMI) treated with ischaemic postconditioning. However, the use of thrombectomy was frequent and thrombectomy may in itself diminish the effect of ischaemic postconditioning. We evaluated the effect of ischaemic postconditioning in patients included in DANAMI-3-iPOST stratified by the use of thrombectomy. Methods: Patients with STEMI were randomised to conventional primary percutaneous coronary intervention (PCI) or ischaemic postconditioning plus primary PCI. The primary endpoint was a combination of all-cause mortality and hospitalisation for heart failure. Results: From March 2011 until February 2014, 1234 patients were included with a median follow-up period of 35 (interquartile range 28 to 42) months. There was a significant interaction between ischaemic postconditioning and thrombectomy on the primary endpoint (p=0.004). In patients not treated with thrombectomy (n=520), the primary endpoint occurred in 33 patients (10%) who underwent ischaemic postconditioning (n=326) and in 35 patients (18%) who underwent conventional treatment (n=194) (adjusted hazard ratio (HR) 0.55 (95%confidence interval (CI) 0.34 to 0.89), p=0.016). In patients treated with thrombectomy (n=714), there was no significant difference between patients treated with ischaemic postconditioning (n=291) and conventional PCI (n=423) on the primary endpoint (adjusted HR 1.18 (95% CI 0.62 to 2.28), p=0.62). Conclusions: In this post-hoc study of DANAMI-3-iPOST, ischaemic postconditioning, in addition to primary PCI, was associated with reduced risk of all-cause mortality and hospitalisation for heart failure in patients with STEMI not treated with thrombectomy. Trial registration number: NCT01435408 .